2013
DOI: 10.1111/j.1743-6109.2012.02725.x
|View full text |Cite
|
Sign up to set email alerts
|

Position Paper: Management of Men Complaining of a Small Penis Despite an Actually Normal Size

Abstract: Introduction With the worldwide increase in penile augmentation procedures and claims of devices designed to elongate the penis, it becomes crucial to study the scientific basis of such procedures or devices, as well as the management of a complaint of a small penis in men with a normal penile size. Aim The aim of this work is to study the scientific basis of opting to penile augmentation procedures and to develop guidelines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
74
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 54 publications
1
74
0
6
Order By: Relevance
“…The racial controversy introduces more variables, which can influence decisions about justifying augmentation phalloplasty. [5,6] The enhancement of penis size can be achieved using surgical or nonsurgical procedures. Unfortunately the uses of unproven techniques or synthetic fillers have made these treatments notorious for their sequelae or bad results.…”
Section: Resultsmentioning
confidence: 99%
“…The racial controversy introduces more variables, which can influence decisions about justifying augmentation phalloplasty. [5,6] The enhancement of penis size can be achieved using surgical or nonsurgical procedures. Unfortunately the uses of unproven techniques or synthetic fillers have made these treatments notorious for their sequelae or bad results.…”
Section: Resultsmentioning
confidence: 99%
“…In a review by Ghanem et al, average penis length was reported as being 12.3 cm stretched and 12.7 cm erect. 6 However, most of the men (or parents bringing children) seeking help for "small penises" do not really present abnormal penis sizes. 6,7 They are just esthetically dissatisfied, 6 and many surgery clinics (urology and plastic) are probably profiting from this dissatisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…6 However, most of the men (or parents bringing children) seeking help for "small penises" do not really present abnormal penis sizes. 6,7 They are just esthetically dissatisfied, 6 and many surgery clinics (urology and plastic) are probably profiting from this dissatisfaction. While this is an issue still under investigation, this complaint has already being named in the literature as "penis dysmorphophobia", 3,6,7 a condition in which men seek medical treatments believing that their penises are too short.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations